2011
DOI: 10.1007/s13277-011-0245-7
|View full text |Cite
|
Sign up to set email alerts
|

Lentivirus-delivered Krüppel-like factor 8 small interfering RNA inhibits gastric cancer cell growth in vitro and in vivo

Abstract: We found that the transcription factor Krüppel-like factor 8 (KLF8) was highly expressed in gastric cancer tissues and cell lines compared with adjacent noncancerous regions and gastric epithelial mucosa cells. We employed a lentivirus-mediated RNAi technique to knockdown KLF8 expression in gastric cancer cell line SGC7901 and observed its effects on cell growth in vitro and in vivo. Knockdown of KLF8 inhibited SGC7901 cell proliferation, promoted cell apoptosis, inhibited the tumorigenicity of SGC7901 cells, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 21 publications
2
24
0
Order By: Relevance
“…Various KLF8 transcripts have been identified, and the relative levels of the transcript expression appear to be similar to that in various tissues. In a previous study, we confirmed that KLF8 is important in SGC7901 gastric cell progression in vitro and in vivo (12). However, its underlying role in SGC7901 cells with invasion and migration under normoxic or hypoxic conditions have yet to be adequately elucidated.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…Various KLF8 transcripts have been identified, and the relative levels of the transcript expression appear to be similar to that in various tissues. In a previous study, we confirmed that KLF8 is important in SGC7901 gastric cell progression in vitro and in vivo (12). However, its underlying role in SGC7901 cells with invasion and migration under normoxic or hypoxic conditions have yet to be adequately elucidated.…”
Section: Discussionsupporting
confidence: 68%
“…A non-targeting stem-loop DNA PsicoR vector was generated as a negative control. Lentiviral particles were prepared as previously described (12). Gastric cancer cells were infected with KLF8 cDNA, siRNA-lentivirus or negative control virus at 7 days and examined at 10 days.…”
Section: Klf8 Cdna Vector and Rnai Lentivirus Generationmentioning
confidence: 99%
See 1 more Smart Citation
“…As a GT-box (CACCC) binding dual-transcription factor, KLF8 regulates the transcription of numerous genes by recruiting the C-terminal binding protein (CtBP) corepressor (6-10) or p300 and P300/CtBP-associated factor histone acetyltransferase co-activators (8,(11)(12)(13)(14) in order to target gene promoters. It is aberrantly overexpressed in a number of cancer subtypes and has been implicated in the initiation, development and progression of these cancer subtypes, including hepatocellular carcinoma (15)(16)(17), gastric cancer (18)(19)(20)(21), breast cancer (22,23), ovarian cancer (14,24), renal cancer (22,25) and glioma (26). It is worth noting that KLF8 induced tumor cell epithelial-to-mesenchymal transition (EMT) and maintained the invasive potential of cancer, which appeared to serve a critical role in the metastatic progression of cancer cells (6,27).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, KLF8 has been shown to activate transcription from some gene promoters (21)(22)(23)(24). KLF8 is not expressed at readily detectable levels in most cell and tissue types studied to date (55), but numerous studies have reported its upregulation in various human cancers, including prostate (56), gastric (57,58), hepatocellular (59,60), glioma (61), breast (62,63), renal (64), and ovarian (65). KLF8 has been shown to regulate oncogenesis by promoting cellular proliferation and tumor invasion and by inhibiting apoptosis (21,(65)(66)(67)(68) Crossing these mice with Klf3 null mice results in embryonic lethality, indicative of a genetic interaction between these two factors.…”
mentioning
confidence: 99%